Implementation of Deep Scaffolding Based on Realistic Mathematics Education to Improve Thinking Errors of Students with Mild Intellectual Disabilities in Solving Numeracy Problems - Wibawa, Kadek Adi; Atmaja, I Made Dharma; Widarnandana, I Gde Dhika (International Journal of Learning, Teaching and Educational Research, 2025)
Students with mild intellectual disabilities (MID) often struggle with numeracy concepts, particularly in representing geometric forms, performing arithmetic operations and applying mathematics to real-life contexts. This study aimed to examine how deep scaffolding grounded in Realistic Mathematics Education (RME) could remediate thinking errors of MID students in solving contextual numeracy problems. Using an interpretative qualitative approach with an exploratory single-case study design, one student (S1) with MID was selected from 61 participants identified through the Culture Fair Intelligence Test (CFIT). Data were collected through contextual numeracy worksheets, semi-structured interviews and observation, then analysed thematically using the mindful–meaningful–joyful scaffolding framework. The results revealed a significant transformation in S1’s cognitive and emotional engagement. Initially, S1 was unable to represent or solve contextual problems. Through mindful scaffolding, S1 identified and corrected reasoning errors; meaningful scaffolding helped link prior experiences to mathematical contexts; and joyful scaffolding fostered confidence and reflective awareness. By the final session, S1 successfully solved multi-step numeracy tasks and demonstrated improved metacognitive and spatial reasoning abilities. This study highlights that deep scaffolding, when integrated with RME, not only enhances conceptual understanding but also promotes emotional resilience and reflective learning in students with MID. Theoretically, it expands Freudenthal’s progressive mathematisation by incorporating affective and metacognitive dimensions. Practically, it offers an inclusive pedagogical model that can guide teachers in designing empathetic, contextual and transformative numeracy instruction for diverse learners. https://doi.org/10.26803/ijlter.24.12.28